Cost-Effectiveness of 1-Time Universal Screening for Chronic Hepatitis B Infection in Adults in the United States. (6th May 2021) - Toy, Mehlika; Hutton, David; Harris, Aaron M; Nelson, Noele; Salomon, Joshua A; So, Samuel
Abstract: Background: An estimated 862 000 to 2.4 million people have chronic hepatitis B infection (CHB). Hepatitis B screening is recommended for pregnant women and populations with increased CHB risk. However, diagnosis rates remain low, with only 33% of people with CHB aware of their infection. This study aimed to assess the cost-effectiveness of universal adult screening for CHB. Methods: We used a Markov model to calculate the costs, population health impact, and cost-effectiveness of 1-time universal screening and CHB monitoring and treatment compared with current practice. Sensitivity analysis was performed on model parameters to identify thresholds for cost-saving or cost-effectiveness based on a willingness to pay of $50 000/quality-adjusted life-year. The analysis assumed testing would be performed during routine healthcare visits and that generic tenofovir or entecavir would be dispensed for treatment. Testing costs were based on Medicare reimbursement rates. Results: At an estimated 0.24% prevalence of undiagnosed CHB, universal hepatitis B surface antigen (HBsAg) screening in adults aged 18–69 years is cost-saving compared with current practice if antiviral treatment drug costs remain below $894/year. Compared with current practice, universal screening would avert an additional 7.4 cases of compensated cirrhosis, 3.3 cases of decompensated cirrhosis, 5.5 cases of hepatocellular carcinoma, 1.9 liver transplants, and 10.3 hepatitis B virus–related deaths at a saving of $263 000/100 000 adults screened. Conclusions: Universal HBsAg screening of adults in the US general population for CHB is cost-effective and likely cost-saving compared with current CHB screening recommendations. Abstract : Universal hepatitis B surface antigen screening of adults for chronic hepatitis B in the United States is likely cost-saving and will result in better health outcomes compared with current practice if antiviral treatment drug costs remain below $894 per year.